A história da escola estadual comunitária rural de Colatina: relatos de protagonistas - Rosângela Pereira de Oliveira; Ozerina Victor de Oliveira (EccoS – Revista Científica)
The text reports the research on the history of the Colatina Rural Community School (EECOR). The problematization is centered in the debate about the possibility of a school linked to the State constituting itself in a decolonial perspective and in the understanding of the strategies of construction of an investigative process with that sense. The epistemological support of research is related to historical-critical analysis, history as a movement in which social processes relate and transform intrinsically, and in a theoretical approach aligned to the conceptions of the epistemologies of the South and Freirian pedagogy. The methodology of the study comprised a qualitative approach using participant research, in a theoretical and practical perspective that assumes research as a collective production of knowledge. The instruments chosen were the analysis of documents and the narrative interviews with the main protagonists of the process of constitution of the school, from which the categories of analysis were constituted. The results indicate that the Alternation Pedagogy1 can provide resistance practices that contribute to the construction of a decolonial perspective for Field Education.